PEMBUATAN, KARAKTERISASI DAN PENETAPAN KINERJA FARMASETIKA KRISTAL MULTIKOMPONEN LEVOFLOKSASIN MONOHIDRAT-ASAM SALISILAT - Simak, Sonia
Levofloxacin is a fluoroquinolone antibacterial compound which is slightly soluble in water. Cocrystal in pharmacy is an important approach for optimizing the physicochemical properties of pharmaceutically active ingredient molecules. This research aims to produce cocrystal levofloxacin monohydrate (LM) with salicylic acid coformer (AS) which is expected to have better solubility to increase the bioavailability of levofloxacin. This research was initiated by making a physical mixture of LM-AS (1:1) with various molar comparisons and tested using electrothermal, which indicates that cocrystal will form at a ratio of 1:1. Then, the solvent is optimized by using ethanol, methanol, and water as solvents. The multicomponent system was characterized using FTIR spectroscopy, thermal analysis using electrothermal and DTA/TG, diffraction analysis using PXRD, and structure analysis using 1 H NMR. Finally, the solubility test is performed on the multicomponent system to compare the performance of the multicomponent system against a single LM. Specific peaks in FTIR characterization are 1709, 1624, 1535, and 3433 cm -1 which indicate the formation of intermolecular hydrogen bonds between LM-AS carboxylic acid groups. In NMR analysis, the involvement of hydroxyl protons in strong hydrogen bonds to the study of NMR conformations in solution presents an experimental challenge because of the rapid chemical exchange between hydroxyl groups and H2O residues in aprotic solvents. Thermal analysis showed endothermic peaks at 216.262°C and 265.219°C, which represent melting point and total crystal decomposition. Diffractogram revealed several peaks with high intensity at diffraction angle values of 4.26°C; 12.05°; 13.33°; 14.87°; 17.25°; 18.22°; 22.00° and 25.83° which differ from every single component. All the results of the characterization analysis suggested that the multicomponent system obtained was a new crystalline phase, suspected to be cocrystal. To obtain an efficient process, the solubility test is carried out with cocrystal made by fast evaporation (FE) method and in a medium of pH 1.2, pH 6.8, and water. From the solubility test results, the solubility of the multicomponent system at all pH showed a decrease in solubility, with the level of cocrystal solubility equal with increasing pH of the medium.